1985
DOI: 10.1080/03079458508436223
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effects of Ochratoxin a in young Turkeys1

Abstract: SUMMARYOchratoxin A (OA), a potent nephrotoxic mycotoxin, was fed to day-old turkey poults at 0 and 4 parts/10 6 dietary levels for 4 and 10 weeks, and its effects, particularly on the immune system, were studied. OA resulted in a significant retardation of growth in both males and females. OA caused a regression of the thymus and bursa of Fabricius and lymphoid depletion in these and other lymphoid organs. Analysis of covariance revealed an enlargement of the kidneys at 10 weeks of age in OA-treated birds; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 16 publications
5
14
0
Order By: Relevance
“…Several studies revealed that OTA affected the structural components of the immune system. Immune suppression due to regression of immunological organs such as the bursa of Fabricius and the thymus and their lymphoid cell population in the OTA treated chicks, resulted in a decline in IgG, IgA and IgM levels in serum (Dwivedi and Burns, 1985). This result lends further support to the present findings.…”
Section: Humoral Immune Responsesupporting
confidence: 81%
See 1 more Smart Citation
“…Several studies revealed that OTA affected the structural components of the immune system. Immune suppression due to regression of immunological organs such as the bursa of Fabricius and the thymus and their lymphoid cell population in the OTA treated chicks, resulted in a decline in IgG, IgA and IgM levels in serum (Dwivedi and Burns, 1985). This result lends further support to the present findings.…”
Section: Humoral Immune Responsesupporting
confidence: 81%
“…The stimulation index of the lymphocyte transformation test in rabbits indicated a significantly lower cellular immune response in OTA and combination groups. This may be due to the effect of these toxins on the immunocompetent organs (Chang, 1979;Dwivedi and Burns, 1985). These findings were further supported by a reduced cellular reaction in the dermis at the skin test site, as histopathologically noted.…”
Section: Cell Mediated Immune Responsesupporting
confidence: 67%
“…The finding of our study is in line with results shown by Elaroussi et al (2006) that reported significant decreases in the skin thickness response to PHA-P in male broiler chicks kept on an OTA-contaminated ration (i.e., at 0.4 and 0.8 mg/Kg diet) for 5 weeks. The significant decrease in the thymus weight and depletion of lymphoid cells noted here-and also reported earlier by Elauorssi et al (2006), Al-Anati andPetzinger (2006), andDwividi andBurns (1985)-provide significant clues to allow us to better understand the depression in T-lymphocyte functions in OTA-treated birds.…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, OTA fed to broilers alone (4 parts/ 10 6 ) decreased humoral immunity, and in combination with aflatoxin (2 parts/10 6 ) decreased humoral and cellular immunity (Verma et al ., 2004). OTA was detrimental also to quail (Farshid & Rajan, 1996) and turkey immunity (Dwivedi & Burns, 1985). Suppression of humoral and cellular immunity by OTA reduces the immune response of chickens to vaccination against Newcastle disease virus strain B1 (Stoev et al, 2000(Stoev et al, , 2002 or LaSota strain (Santin et al ., 2002), and allows development of secondary bacterial infections (Kumar et al ., 2003(Kumar et al ., , 2004 Two findings that were reported in this study, a reduced leucocyte count and thymus weight, implied that the functioning of the immune system is altered.…”
Section: Discussionmentioning
confidence: 99%